Salt taste perception, dietary salt intake, cardiovascular health and genetic variation in Zambian adults with HIV - Masenga, Sepiso K.; Graham, Catherine A.-M.; Nixon, Jonathan; Povia, Joreen P.; Kirabo, Annet; Pilic, Leta (Frontiers in Physiology, 2025)
IntroductionCardiovascular diseases (CVDs) are the leading cause of noncommunicable mortality in sub-Saharan Africa (SSA), driven in part by excessive salt intake. People living with HIV (PLWH) face heightened CVD risks due to hypertension and potential taste dysfunction, yet genetic and sensory drivers of salt intake in this population remain understudied. This study primarily explores differences between salt taste perception and dietary salt intake. The secondary aim was to determine if genetic variation influences the above and health markers of CVD.MethodsSeventy-nine Zambian adults (37 PLWH, 42 healthy controls (HC)) underwent salt taste threshold/preference assessments, 24-h dietary recalls, and genotyping. Salt intensity/pleasantness was rated using visual analogue scales, and area-under-the-curve (AUC) values were calculated. Systolic and diastolic blood pressure, pulse rate, and body mass index (BMI) were measured.ResultsPLWH consumed more salt than HC (median: 9.01 vs. 7.11 g/day, p = 0.041) and exhibited reduced salt intensity perception (AUC: 94.8 vs. 109.2, p = 0.02). Genetic analyses revealed that PLWH with the TRPV1 rs4790522 AC/CC genotype consumed more salt (9.4 vs. 7.3 g/day, p < 0.05) and those with the AA genotype had lower BMIs than HC (21.0 vs. 27.9 kg/m2, p = 0.001). The SCNN1B rs239345 AT/AA genotype in PLWH was linked to elevated systolic/diastolic blood pressure (142.0/92.0 mmHg) at high salt intake. No direct correlations emerged between taste thresholds and salt intake (p > 0.05).ConclusionPLWH consumed more salt than HC, which may be driven by a reduced salt perception. Additionally, differences were found in the association between the TRPV1 rs4790522 SNP, salt intake and BMI profiles, between PLWH and HC, suggesting a gene-environment-disease interaction. Future research should validate these associations in larger cohorts and explore interventions addressing genetic and sensory contributors to hypertension in high-risk SSA populations.